1996
DOI: 10.1038/bjc.1996.206
|View full text |Cite
|
Sign up to set email alerts
|

Increased insulin-like growth factor binding protein-2 (IGFBP-2) gene expression and protein production lead to high IGFBP-2 content in malignant ovarian cyst fluid

Abstract: Summary Expression of insulin-like growth factor-I (IGF-I), its receptor and IGF-binding proteins (IGFBPs) by ovarian cancer cells and its mitogenic effect on these cells in vitro, suggest that IGF-I may have a role in regulation of human ovarian cancer. We have recently shown IGFBP-2 to be markedly elevated in malignant ovarian cyst fluid in vivo. To identify the origin of increased IGFBP-2 in these cyst fluids, the gene expression and protein content of IGFBP-2 were investigated in 14 malignant and four beni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
26
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(30 citation statements)
references
References 17 publications
4
26
0
Order By: Relevance
“…These findings are consistent with a previous observation that increases in serum IGFBP2 are caused mainly by the markedly increased production of IGFBP2 by tumor cells in vivo. 10 In addition, some studies have shown that patients with malignant ovarian tumors have significantly higher serum levels of IGFBP2 compared with benign controls. 11,12 In contrast, only 18% of clear cell carcinomas and 37% of mucinous ovarian carcinomas showed moderate to strong staining for IGFBP2.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings are consistent with a previous observation that increases in serum IGFBP2 are caused mainly by the markedly increased production of IGFBP2 by tumor cells in vivo. 10 In addition, some studies have shown that patients with malignant ovarian tumors have significantly higher serum levels of IGFBP2 compared with benign controls. 11,12 In contrast, only 18% of clear cell carcinomas and 37% of mucinous ovarian carcinomas showed moderate to strong staining for IGFBP2.…”
Section: Discussionmentioning
confidence: 99%
“…8,9 Among the IGFBPs expressed in ovarian cancers, IGFBP2 is markedly increased and significantly higher in cystic fluid from malignant epithelial ovarian tumors than in cystic fluid from benign epithelial ovarian tumors, mainly due to the increase in mRNA and protein expression in the tumor cells. 10 Serum IGFBP2 levels are also significantly higher in patients with ovarian cancer compared with benign controls. 11,12 Serum IGFBP2 levels in patients with ovarian cancers correlates positively with the ovarian tumor marker, CA-125.…”
mentioning
confidence: 95%
“…Accumulating evidence supports the idea that IGFBP2 might act as a promoter, rather than a tumor suppressor, in EOC. This evidence includes the overexpression of both the IGFBP2 gene and protein in malignant ovarian cyst fluid (Kanety et al 1996), activated cell invasion in response to IGFBP2 induction (Lee et al 2005), and the concurrent elevation of IGFBP2 levels in EOC tumor tissues and serum (Lancaster et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…IGFBP-3 is the primary binding protein of IGF-I and levels seem to be lower in women with ovarian cancer versus benign lesions (5)(6)(7)(8). IGFBP-2 is commonly overexpressed by ovarian cancer cells (11)(12)(13), and retrospective studies report higher IGFBP-2 levels in cases versus controls (5,7,8). However, prospective studies have not observed an association between these binding proteins and ovarian cancer risk (3,4,14).…”
Section: Introductionmentioning
confidence: 99%